Pelaksanaan konsep peraturan kendiri dan pensijilan kendiri dalam kaedah pengeluaran sijil siap dan pematuhan - Khalid, Khairil (2013)
Certificate of completion and compliance (CCC) was introduced in view of public service delivery system improvement towards transparency, speedy and efficiency to increase national productivity, improve investor confidence in property development as well as upholding people well-being. In CCC, instead of Local Planning Authority (LPA), competent person from professional consultants was given the responsibility to certified on the completion and safety of building. Through self-regulation and certification, the competent persons are required to adhere high standard of professionalism to ensure the success of CCC practice. Hence, the amendment of acts such as Road, Street and Building Act, 1974 (Act 133), Uniform Building by Law, 1984 (UBBL), Architect Act 1967 (Act 117) and Engineer Registration Act, 1967 transferred this accountability to the professional consultants. Nevertheless, inspection and enforcement from LPA and professional bodies must be done to ensure committed non-compliance actions are effectively supervised and stopped. This research is to study the effectiveness of self-regulation and certification concept by Principle Submitting Person (PSP) through CCC implementation. An audit on approved building plan application and project site inspection was done to inspect the completion of building and its CCC status. The study also covers level of PSP and LPA understanding on the process and procedure of CCC issuance, PSP and LPA roles and responsibilities, and CCC related offences as described in the act. Based on research findings, there are few things was not conformed with procedures due to the lack of LPA and PSP understanding on CCC or intentionally not comply because of the opportunity to do so